Individual variants of emotional stability of athletes - Rodionov, A. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. I, 2008)
Introduction: The present study is an attempt to determine the effect of stress tolerance on special abilities to operative task solving in different emotional states, and thus on effectiveness of sport activity. These abilities are displayed in the quickness of information perception and corresponding motor activity, which sometimes is defined as "operative intellect" [1] manifestation. "Operative intellect" is for the most part determined by such integral property as emotional stability. It is defined as the ability of an athlete to keep and enhance mental and physical capacity under the influence of strong emotional factors. Emotional stability is a stable psychic quality of a person; it is being formed in sport activity, but the specificity of its formation is determined by individual traits of the athlete. Methods The elite fencers (n = 46) were differentiated by the classic Uznadze`s set fixation method [2]. Complex method for emotional tension and emotional stability testing included: 1) seismotremorgraphic method for tremor amplitude and frequency registration, 2) Galvanic Skin Response (GSR) registration, 3) classical electric reflex metric method, 4) anamneses and psychicpedagogical observation. The reflex metric data were assessed, as, on one hand, emotional tension and on the other hand, as the criteria for successfulness of competitive activity of fencers in emotionally intense situations.